Internalisasi Nilai Tradisi Budaya Banten Dalam Pembelajaran Bahasa Indonesia Di Sekolah Dasar - Yoma Hatima; Ana Nurhasanah (Prodi PGSD Unsultra, 2026)
This study aims to describe the internalization of Bantenese cultural traditions in Indonesian language learning at elementary schools through a literature review approach. This study is important as an effort to preserve local wisdom while strengthening students’ language skills and character education in the era of globalization. The method used was descriptive qualitative with a literature review of journals, books, articles, and relevant educational documents. Data were analyzed through identification, classification, interpretation, and conclusion drawing. The results show that Bantenese cultural traditions can be integrated into Indonesian language learning through folklore, oral traditions, traditional games, regional arts, and local expressions in reading, writing, speaking, and listening activities. These cultural values include religiosity, cooperation, politeness, responsibility, and respect for others, which support character education for elementary school students. In addition, culture-based learning creates a more contextual, meaningful, and engaging learning process because it is closely related to students’ daily lives. Teachers play an important role in creatively integrating local culture into teaching materials and classroom activities. Therefore, the internalization of Bantenese cultural traditions can serve as an effective alternative in improving students’ language competence while preserving local culture and strengthening character education from an early age.